Learning from previous work and finding synergies in the domains of public and environmental health: EU-funded projects BRIDGE Health and HBM4EU - Madlen David; Gerda Schwedler; Lena Reiber; Hanna Tolonen; Anna-Maria Andersson; Marta Esteban López; Anke Joas; Miriam Schöpel; Alexandra Polcher; Marike Kolossa-Gehring (BMC, 2020)
Abstract Background During the last decade, the European Union initiated several projects in the domains of public and environmental health. Within this framework, BRIDGE Health (Bridging Information and Data Generation for Evidence-based Health policy and Research) and HBM4EU (European human biomonitoring initiative) have been implemented. Whereas, the focus of BRIDGE Health was towards a sustainable and integrated health information system (HIS), the aim of HBM4EU is to improve evidence of the internal exposure of European citizens to environmental chemicals by human biomonitoring (HBM) and the impact of internal exposure on health. As both, environmental and public health determinants are important for health promotion, disease prevention and policy, BRIDGE Health and HBM4EU have overlapping aims and outcomes. In order to improve health information regarding public health and environmental health issues, best use and exchange of respective networks and project results is necessary. Methods Both projects have implemented health information (HI) and HBM tasks in order to provide adequate environmental and public health information of the European population. Synergies of the projects were identified in the working progress and because of overlapping networks and experts a focused analysis of both projects was envisaged. This paper elaborates on the aims and outcomes of both projects and the benefit of merging and channelling research results for the use of better health information and policy making that may be of relevance for any other project in these research fields. Results The need for focused exchanges and collaborations between the projects were identified and benefits of exchanges were highlighted for the specific areas of indicator development, linkage of data repositories and the combination of HBM studies and health examination surveys (HES). Further recommendations for a European wide harmonisation among different tasks in the fields of public health and environmental health are being developed. Conclusions Lessons learned from HBM4EU and BRIDGE Health show that continuous efforts must be undertaken, also by succeeding projects, to guarantee the exchange between public health and environmental health issues. Networks covering both are essential to provide better evidence of knowledge. The experiences from BRIDGE Health and HBM4EU give a valuable input for any future activity in these domains. Avoiding overlaps and streamlining further exchange of public health and environmental health contributes to best use of research results and allows to develop new strategies and tools for improvement of health information and thus enhances people's health and well-being.